2021
DOI: 10.1021/jacs.1c04424
|View full text |Cite
|
Sign up to set email alerts
|

Bimolecular Coupling in Olefin Metathesis: Correlating Structure and Decomposition for Leading and Emerging Ruthenium−Carbene Catalysts

Abstract: Bimolecular catalyst decomposition is a fundamental, long-standing challenge in olefin metathesis. Emerging ruthenium–cyclic(alkyl)(amino)carbene (CAAC) catalysts, which enable breakthrough advances in productivity and general robustness, are now known to be extraordinarily susceptible to this pathway. The details of the process, however, have hitherto been obscure. The present study provides the first detailed mechanistic insights into the steric and electronic factors that govern bimolecular decomposition. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 74 publications
1
63
0
Order By: Relevance
“…This can be explained by the intrinsic decomposition of the metathesis catalysts via β-elimination, leading to RuÀ H species inducing double-bond isomerization. [24][25][26] The positive effect of increasing RuH loading on propylene yield showed that the "bottleneck" of propylene formation is certainly the rate of isomerization. The purity of the ethylene gas used strongly influenced the ISOMET activity of the catalysts.…”
Section: Zuschriftenmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by the intrinsic decomposition of the metathesis catalysts via β-elimination, leading to RuÀ H species inducing double-bond isomerization. [24][25][26] The positive effect of increasing RuH loading on propylene yield showed that the "bottleneck" of propylene formation is certainly the rate of isomerization. The purity of the ethylene gas used strongly influenced the ISOMET activity of the catalysts.…”
Section: Zuschriftenmentioning
confidence: 99%
“…[22,23] These intermediates, when heated in the presence of ethylene excess, may take part in β-elimination reactions and lead to fast intrinsic catalyst decomposition. [24][25][26] The recent development of new carbene ligands has resulted in catalysts with higher stability, functional group tolerance, and improved catalytic activity (Scheme 2). [27][28][29][30][31][32] For example, replacing the N-heterocyclic carbene (NHC) ligand of the second generation Hoveyda-Grubbs catalyst (HG2) by CAAC-5 carbenes significantly improves the efficiency of olefin metathesis (Scheme 3, BG).…”
mentioning
confidence: 99%
“…While chlororuthenium catalysts (Chart ) dominate these applications, iodide analogues offer important advantages. Long-overlooked because of their slower metathesis reactions, iodide catalysts such as nG-I 2 have recently been shown to offer improved productivities in the synthesis of macrocycles via ring-closing metathesis (mRCM, , a metathesis manifold of keen interest for the production of antiviral therapeutics), and increased selectivity for metathesis of terminal versus internal olefins . Their tolerance for ethylene , (the coproduct in metathesis of terminal olefins) is also striking: it is due in part to relatively slow bimolecular decomposition. , Indeed, their ethylene-tolerance is second only to that of cyclic (alkyl)­(amino) carbene (CAAC) derivatives, examples of which appear in Chart . , Heightened stability toward water adds further potential, most prominently for opportunities in chemical biology.…”
mentioning
confidence: 99%
“…The new catalysts hold intriguing potential in mRCM in view of evidence that bulky ligands accelerate cyclization of conformationally flexible dienes (e.g., musk precursor 2 ; Table ). Also important is the slower bimolecular decomposition of RuI 2 (L)­(CH 2 ) . Catalyst lifetime is critical for such mRCM reactions because cyclization typically proceeds via a concentration-dependent ring–chain equilibrium, in which oligomerization is kinetically preferred and the oligomers liberate the desired products via backbiting .…”
mentioning
confidence: 99%
See 1 more Smart Citation